ANALISIS KEGIATAN P5 TEMA “BHINNEKA TUNGGAL IKA” SEBAGAI PENERAPAN KURIKULUM MERDEKA SMK NEGERI 2 SEMARANG - Pratama, Aldino Pratama; Titik Haryati; Puput Tri Hartanti; Suharmanto (Jurnal Tunas Pendidikan, 2024)
` This research aims to find out about the implementation of P5 activities with the theme "Bhinneka Tunggal Ika" as a project to increase the profile of Pancasila students in schools and the impact of its implementation on students. The research was conducted using qualitative methods with a descriptive approach. This research was conducted at SMK Negeri 2 Semarang. P5 activities are part of the independent curriculum, this P5 activity is carried out every semester. P5 activities with the theme "Bhinneka Tunggal Ika" have had a positive impact on students such as character development, development of students' soft skills, fostering a spirit of nationalism, and an attitude of love for the homeland. The obstacles or constraints in implementing P5 are funding, however, the implementation of P5 activities with the theme "Bhinneka Tunggal Ika" is running well and has a positive impact on both students and schools.